THE INFLUENCE OF THE TECHNOLOGICAL ENVIRONMENT ON THE MECHANICAL WEAR OF THE WORKING ORGANS OF THE MACHINE - Стадник, Ігор; Деркач, Андрій; Кравченюк, Христина; Федорів, Віктор (SWorldJournal, 2024)
The considered environment with the composition of chemical and surface-active substances, which, falling on the cylindrical surface of the working bodies, cause corrosive destruction and wear or corrosion-mechanical activation. Since friction is always